Peran Kompetensi Profesional Guru PAUD dalam Meningkatkan Kualitas Pembelajaran Berbasis Teknologi. - Ayesha Nayra E.; Mutia Sandrina; Rifa Aska Auliya; Sherly Purnama Sari; Rita Kurnia; Asfi Yanti WE (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
This study aims to describe the professional competence of Early Childhood Education (ECE) teachers in implementing technology-based learning at PAUD “X”. Teacher professionalism plays a crucial role in determining the quality of early childhood learning, particularly in the digital era where educators are expected to adapt to technological advancements. This research employs a descriptive qualitative approach, utilizing observations and semi-structured interviews to obtain an in-depth understanding of teachers’ abilities in managing learning processes, mastering instructional content, and integrating appropriate learning media. The findings indicate that teachers demonstrate strong pedagogical, social, and personal competencies. They successfully create an engaging and developmentally appropriate learning environment, use language that is easily understood by young children, and exhibit patience, discipline, and effective communication skills. Positive interaction among teachers, children, and parents contributes to a supportive and collaborative learning atmosphere. Teachers also incorporate simple learning materials, such as origami and visual aids, to enhance student engagement. Nevertheless, the study reveals that teachers’ professional competence in utilizing digital technology remains limited. Although technological tools are available, several teachers lack confidence and technical skills in operating digital devices, such as projectors and interactive media. Insufficient training and mentoring are identified as primary barriers. The study concludes that strengthening teachers’ technological competence should be prioritized through continuous professional development programs, including structured training and peer mentoring. Enhanced technological skills will enable teachers to design learning experiences that are more interactive, innovative, and responsive to the developmental needs of young children.